Occludin acts as a dynein adaptor regulating permeability and collateral angiogenesis - Xuwen Liu; Enming J. Su; Alyssa Dreffs; John P. Gillies; Madeline Merlino; Lu Gao; Julian S. Peregoff; Cheng-mao Lin; Margaret Elizabeth Ross; Morgan E. DeSantis; Daniel A. Lawrence; David A. Antonetti (Proceedings of the National Academy of Sciences, 2025)
Previous studies of the tight junction protein occludin (OCLN) suggest that multiple phosphorylation sites on the carboxy-terminal domain contribute a regulatory role in vascular barrier properties. However, gene deletion studies failed to identify a clear functional role for OCLN, despite multiple phenotypic alterations. Importantly, previous studies targeting exon 3 allowed expression of a splice variant starting at exon 4 (isoform 4), that expresses the full carboxy-terminal tail. Here we show that the OCLN carboxy terminus forms a complex with the light intermediate chain (LIC) of dynein to link tight junction cargo to the minus end directed motor protein. Mutational analysis revealed S471 phosphorylation promotes binding to the LIC while S490 phosphorylation is required for trafficking. Expressing OCLN S490A mutant prevented endothelial cell proliferation and collateral angiogenesis. Ocln gene deletion targeting exon 5, preventing full-length and isoform 4 expression, resulted in embryonic lethality. In summary, OCLN links tight junction cargo to the dynein motor, regulating trafficking in a phosphorylation-dependent manner and contributing to both vascular endothelial growth factor-induced vascular permeability and collateral angiogenesis.